Halalan Toyyiban Concept as Religious-Based Intervention for Healthy Diet among Youth - Zakaria, Rasinah; Ahmad, Anis Najiha; Nordin, Noor Faizul Hadry; Samsudin, Nurhusna; A M Elgharbawy, Amal; Pengiran Hashim, Pengiran Norkhairiah (Halalsphere, 2024)
Healthy youth eating habits are crucial for optimal growth and development. It helps build a strong immune system and reduces the risk of chronic diseases. In Islam, there is a focus on maintaining a healthy lifestyle, including a healthy diet, guided by the Qur’an and the teachings of Prophet Muhammad (ﷺ). The article uses a narrative review to highlight the potential applicability of the halalan toyyiban concept (as a faith-based intervention) to promote a healthy diet among youth. Faith-based intervention involves integrating religious beliefs into the intervention process. To provide context, this article explores the application of interventions such as multimodal nutrition education and digital approaches to improve dietary habits among youth. Various interventions targeting university students’ dietary habits yielded mixed results. This highlights the necessity for multifaceted intervention approaches. The article posits combining the halalan toyyiban concept with digital technology to enhance university students’ healthy dietary practices.